DOUBLE TAXATION AVOIDANCE TREATY AND ITS IMPACT IN INDIA - V. VIGNESWAR, Dr. K. KIRUBAGARAN (International Journal of Advanced Science and Technology, 2020)
Double taxation is the imposition of two or more taxes on the same income assets or financial transactions. The League of Nations initiated model legal texts for double tax avoidance agreements in bilateral conventions in 1928. India introduced two provisions related to double tax avoidance in Income Tax Act, 1961. The major objectives of the study is to analyse the benefits of double taxation avoidance treaty and to  study the awareness regarding the legality of the double taxation avoidance treaty and to  compare the status of double taxation avoidance in India with other countries. The study used primarily data and collected from 200 respondents with convenient sampling.research method followed here is empirical research. The samples were collected through a convenient  sampling method.  The study shows that double taxation avoidance treaty provides benefit but fails due to improper implementation.